Relative age effect and gender differentiation within sport - a systematic review - Babic, M.; Macan, I.; Bešlija, T.; Kezic, A.; Tomljanovic, M.; Subašic, L.; Cular, D. (Acta Kinesiologica, 2022)
Success in sports depends on several factors. One of those factors is a psychological and physical advantage, or in other words psycho-physical maturity. Relative age effect (RAE) is one of the phenomenons which can give advantages or disadvantages in sports competitions. Because of this particular effect, many children and young people experience unfair competition conditions. The goal of this study was to detect the difference in RAE existence between genders in sports by analyzing research about RAE in sports, published between 2017 and 2021. Accordingly, scientific databases "Google Scholar", "Web of Science" and "Research Gate" were used for extraction of adequate scientific papers (n=16). Analyzed papers cover a total of 25 sports (14 individual and 11 team sports). Results of this research suggest the greatest impact of RAE among young males (<18 years old), RAE occurs in 81,81% of analyzed samples. The male sample is also affected by RAE, with 85,71% of occurrence among the overall male sample, and 42,86% among the sample composed of males only. There is no significant tendency among females only, while RAE occurs among half of the female samples. The majority of RAE-positive female samples belong to individual sports while the majority of male samples belong to absolute bodyweight sports. No significant differences were found between sports and among the sample of Olympic games competitors. Also, it can be stated that RAE depends on many factors and effects, which can be controlled to a greater extent. Future research should focus on the analysis of the existence of RAE between sports, especially boundaries between groups of sports and among Olympic competitors.